Experience in application of program means for analysis of extremal objects safety - Верюжский, Ю. В. (Proceedings of National Aviation University (archive), 2000)
Analyzed is the experience in application of universal and problem-oriented program means for designing and maintenance of extremal objects. As a typical example we propose solution of a problem of object "Shelter" safety the methodology of which is generalized for investigation of objects of various branches (as well as airport building)